Design and characterization of polarization reconfigurable heart shape monopole antenna for 2.4 GHz application - Abu Hena Murshed; Md. Azad Hossain; Muhammad Asad Rahman; Eisuke Nishiyama; Ichihiko Toyoda (Institute of Advanced Engineering and Science, 2022)
This article represented a heart shape reconfigurable monopole antenna with polarization diversity. The proposed antenna is fed by a 50 Ω microstrip feed line that is printed on a flexible FR-4 (εr=4.4) substrate. The antenna comprises a ring-slot, a cross slot and four positive-intrinsic-negative (PIN) diodes that are soldered on ring slot. Four PIN diodes act as a switch and by controlling these PIN diodes effective current direction is changed hence four various states of polarization are achieved. Four states of polarization such as horizontal linear polarization (H-LP), vertical linear polarization (V-LP), right-hand circular polarization (RHCP) and left-hand circular polarization (LHCP) can be switched easily with the help of these PIN diodes and achieved an efficiency of more than 90%. Proposed antenna shows voltage standing wave ratio (VSWR)<2 at all working frequency and -10 dB reflection coefficients (RC) bandwidths (BW) (i.e., S11≤-10 dB) about 32.86% for linear polarization (LP) states while RHCP and LHCP states possess BW of about 31.61% and 31.67% respectively. It also shows axial ratio (AR) BW of 3.41% and 2.44% for RHCP and LHCP, respectively. Besides, the antenna has a well-suited omnidirectional pattern with a positive gain of all working frequency of interest where cross-polarization level is much lower than that of antenna gain.